New and Simple Method to Prevent Prostate Cancer - Ameri Siahooei, Ali (International Pharmacy Acta, 2018)
Introduction: Men above fifty-five years old are at high risk for malignant prostate cancer. Currently surgery is the only treatment and the patients must use medicines post-operation. This process may exert extreme side effects and reduce their quality of life. On the other hand, in some cases, cancer cells start to multiply again. There is a simple solution for prevention of prostate cancer that we want introduce. Methods and Results: The prostate cancer cells need Glutamine amino acid for their proliferation. Two substances; Ursolic acid and Resveratrol can inactivate some enzymes which prevent reabsorption of Glutamine. Therefore, they can stop cancer cell proliferation. On the other hand, Curcumin can cause apoptosis of cancer cells and destroy them. Ursolic acid, Curcumin and Resveratrol exist in skin of red apple, turmeric and black grapes respectively which are readily available and their consumption together as potion can be useful. Simultaneouse use of Resveratrol and Ursolic acid could extremely reduce danger of prostate cancer by decreasing Glutamine reabsorption in cancer cells. In addition, Curcumin consumption causes apoptosis in cancer cells and destroys them. Therefor we can use it for prevention of prostate cancer. Conclusions: Since the above substances (Resveratrol, Curcumin, Ursolic acid) exist in available compounds like skin of red apple, turmeric and black grapes, men above forty years old can reduce risk of prostate cancer by combining a big apple with some turmeric and black grapes (as a potion) So the prostate would be protected from cancer, After prostate surgery that PSA may raise again. Consumption of this potion in these cases can replace current medications with several side effects. We could combine these materials and determine the amount of dose, same as a drug. In the next step, this combination was tested on animals and humans. Based on human gene plan (HGP) a lack of Allosteric enzymes which by two material Ursolic Acid and Resveratrol will be inactivate and therefore non-proliferation prostate cancer cells.